2020
DOI: 10.33640/2405-609x.1734
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Assessment Model for Hospitals Services Quality based on Patient Experience

Abstract: The patient's experience is a lens for services assessment that provide from healthcare institutions because the patient is the first and the last recipient for the service. The patient's experience carries a lot of uncertainty and an ultimate decision cannot be taken from the patient about the services, but it carries the partial truth. Many artificial intelligence technologies deal with the concept of partial truth, such as genetic algorithms and neural networks, but the fuzzy logic remains pioneering to dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…The findings contradict the literature, which claims that Ghanaian women meet the WHO maternal healthcare requirement by using facilities [2]. Furthermore, the findings revealed that most rural areas in Ghana lack health care centres and trained health care professionals required to provide rural mothers with delivery care, and the findings are consistent with the findings that most rural communities in Ghana lack healthcare facilities and healthcare professionals (Alkafaji & Al-Shamery, [28]).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The findings contradict the literature, which claims that Ghanaian women meet the WHO maternal healthcare requirement by using facilities [2]. Furthermore, the findings revealed that most rural areas in Ghana lack health care centres and trained health care professionals required to provide rural mothers with delivery care, and the findings are consistent with the findings that most rural communities in Ghana lack healthcare facilities and healthcare professionals (Alkafaji & Al-Shamery, [28]).…”
Section: Discussioncontrasting
confidence: 76%
“…The findings proposed that primary healthcare facilities be established in rural communities in order to save the lives of rural women. Mothers should also be encouraged to give birth in a health care facility (hospital/clinic) in the presence of a trained professional health care practitioner such as a midwife, doctor, or nurse (Alkafaji and Al-Shamery, [28]). However, due to a lack of health facilities and qualified trained paramedic staff, the communities studied in Ghana lack professionals capable of providing maternal health care delivery services to mothers during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…This study further supported the earlier work of Komape (2013) who found that age did not have any impact on respondents' preference for public and private healthcare providers. However, the finding contradicted the work of Alkafaji and Al-Shamery (2020) that private health facilities provide quality health services to the elderly compared to public facilities. Older people are more likely to use private hospitals than government hospitals.…”
Section: Discussionmentioning
confidence: 61%
“…Another researcher used a fuzzy analytic hierarchy process to rank the quality of four hospitals [42]. Alkafaji and Al-shemary [43] used the hospital consumer assessment of healthcare providers and systems to collect data from the patients and then applied a fuzzy-based method to assess the hospital service quality for two hospitals in Iraq, and several hospitals in the United States of America. The results of the five assessment categories showed that over half of the US hospitals were in the good to very good range.…”
Section: Literature Reviewmentioning
confidence: 99%